Resiliensi Iman Generasi Strawberry terhadap FoMO: Pendekatan Teologi Berdasarkan 1 Petrus 5:7 - Raymond Hessel Stephen; Yonatan Alex Arifianto (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2026)
The rapid development of the digital age has shaped new social patterns and behaviours among the younger generation, particularly the Strawberry Generation, who have grown up with intense exposure to social media and information technology. This phenomenon has given rise to the Fear of Missing Out (FoMO), which causes anxiety, a sense of insecurity, and even concerns about self-actualisation, and thus has the potential to weaken their spiritual resilience. The lack of contextual pastoral and theological strategies to address FoMO poses a significant challenge for the faith formation of this generation. This study aims to analyse the development of the Strawberry Generation’s faith resilience in the face of FoMO through a theological approach based on 1 Peter 5:7. The research method employs a descriptive qualitative approach involving literature review and theological exegetical hermeneutical analysis. The findings indicate that the theological analysis and exegesis of 1 Peter 5:7 provide a strong foundation for the development of the Strawberry Generation’s faith resilience. An understanding of FOMO within this generation clarifies the psychological and spiritual challenges they face in the digital context. Narrative theology, combined with digital pastoral strategies, has proven effective in guiding and strengthening their faith resilience. Thus, the integration of narrative theology and digital pastoral practices can serve as a contextual, relevant, and practical model for faith formation among young people in the digital age. Abstrak Perkembangan pesat era digital telah membentuk pola sosial dan perilaku baru pada generasi muda, khususnya Generasi Strawberry, yang tumbuh dengan paparan intens terhadap media sosial dan teknologi informasi. Fenomena ini memunculkan Fear of Missing Out (FoMO), yang menyebabkan kecemasan, rasa tidak aman bahkan kuatir akan aktualisasi, dan   sehingga berpotensi melemahkan resiliensi iman mereka. Kurangnya strategi pastoral dan teologis yang kontekstual untuk menghadapi FoMO menjadi persoalan signifikan bagi pembinaan iman generasi ini. Penelitian ini bertujuan menganalisis pembentukan resiliensi iman Generasi Strawberry terhadap FOMO melalui pendekatan teologi berbasis 1 Petrus 5:7. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan studi literatur dan analisis hermeneutic eksegesis teologis. Hasil penelitian menunjukkan bahwa analisis teologis dan eksegesis 1 Petrus 5:7 memberikan landasan kuat bagi pembentukan resiliensi iman Generasi Strawberry. Pemahaman FoMO pada generasi ini memperjelas tantangan psikologis dan spiritual yang mereka hadapi dalam konteks digital. Teologi naratif yang dipadukan dengan strategi pastoral digital terbukti efektif dalam membimbing dan memperkuat ketahanan iman mereka. Dengan demikian, integrasi teologi naratif dan praktik pastoral digital dapat menjadi model pembinaan iman yang kontekstual, relevan, dan aplikatif bagi generasi muda di era digital.